The Metaphors “Human-Animal”, “Animal-Human” in T. Morrison’s Novel “Beloved” - J. G. Timralieva; M. S. Breitling (Дискурс)
Introduction. The study investigates the role of the metaphors “human-animal”, “animalhuman” based on the novel “Beloved” by T. Morrison. The relevance of the research lies in the lack of knowledge of the linguistic specifics of this landmark novel for modern American literature, in the absence of research to identify and analyze key metaphors reflecting the author's conceptualization of reality.Methodology and sources. The authors of this article, relying on semantic and cognitive approaches, consider metaphor as a combination of two planes: linguistic and mental. To describe the mechanism of metaphorical transfers, the article uses the proposed by J. Lakoff and M. Johnson, terms characterizing the interaction of two knowledge structures: the source sphere and the target sphere.Results and discussion. The study showed that the metaphor “man-animal” becomes one of the most productive in the novel. This metaphorical structure includes the following elements of the source sphere: animal names; animal properties; animal body parts; objects characterizing animal activities; actions carried out in relation to animals and animals themselves; people performing actions in relation to animals. The relevance of this metaphor and the variety of sources of transference is dictated by the theme of the novel, comprehending one of the most acute problems of American history – the theme of slavery. The disenfranchised position of a human slave, his “animal” dependence on the slave owner forms the conceptual basis of most metaphorical transfers within this lexical and semantic field. The metaphor “animal-human” is used less often and serves, first of all to enhance the contrast between the life of a human slave and an animal who sometimes feels more confident and freer. This metaphorical structure includes the following elements of the source sphere: forms of addressing a person, the names of the characters in the book, the title of a person, human actions, human properties, objects associated with a person.Conclusion. In the novel “Beloved” by T. Morrison, the metaphor is a significant element of the textual structure reflecting the author's linguistic picture of the world. Especially productive are the mutual likenesses of man and animal, figuratively interpreting the life and attitude of a human slave who is regularly subjected to physical and moral violence.